Smartphone Applications and Website Software Available for Pre-Operative Virtual Rhinoplasty Planning - Levin, Marc; Farhood, Zachary; Asaria, Jamil (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: There are emerging virtual simulation technologies that allow facial plastic surgeons to accurately and objectively show patients how they may appear following rhinoplasty surgery. There is no collective understanding of which virtual rhinoplasty preoperative planning software exist and their associated features. Aim: This article will synthesise information on smartphone and web-based resources for virtual rhinoplasty planning to provide facial plastic surgeons with an up-to-date understanding of the available technologies. Methods: This was a cross-sectional website and smartphone application software review. The Apple App Store and the Google Play were searched for smartphone applications and the Google search engine was searched for website software. Results: Five websites and six smartphone applications met inclusion criteria. Software features included self-directed simulation, in-app purchases, multiple languages, three-dimensional facial rendering and patient-specific perioperative planning. Conclusion: Many smartphone and website based software exist for surgeons to plan their patients’ rhinoplasties. Further data is needed to understand how facial plastic surgeons and patients perceive this software.